Fit for the Presidency? : Winners, Losers, What-Ifs, and Also-Rans - Morris, Seymour (Book collections on Project MUSE., 2017)
Every four years Americans embark on the ultimate carnival, the Super Bowl of democracy: a presidential election campaign filled with endless speeches, debates, handshakes, and passion. But what about the candidates themselves? In Fit for the Presidency? Seymour Morris Jr. applies an executive recruiter's approach to fifteen presidential prospects from 1789 to 1980, analyzing their resumes and references to determine their fitness for the job. Were they qualified? How real were their actual accomplishments? Could they be trusted, or were their campaign promises unrealistic? The result is a fresh and original look at a host of contenders from George Washington to William McAdoo, from DeWitt Clinton to Ronald Reagan. Gone is the fluff of presidential campaigns, replaced by broad perspective and new insights on candidates seeking the nation's highest office.